1982
DOI: 10.1037/0012-1649.18.5.704
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity and novelty preferences in infant recognition memory: Implications for information processing.

Abstract: Some investigators have suggested that young infants show a preference for familiar stimuli, which is supplanted by a preference for novel stimuli as they get older and the act of recognition becomes commonplace. We have carried out two studies that fail to support this developmental view but suggest instead that shifts in preference reflect phases in information processing that occur within a given age; it is only the speed of processing that changes across ages. In the first study, infants aged 3'/2, 4 ! /a,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
237
2
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(266 citation statements)
references
References 29 publications
26
237
2
1
Order By: Relevance
“…Based on pilot work involving 11 infants who received recognition tests identical to those in the present study, the Pearson coefficient of correlation between observed fixation times was .93, with almost identical totals for mean fixation times recorded by the two observers. This agreement is typical in laboratories using the same apparatus and measurement procedures (see Fagan, 1976, andRose et al, 1982). measures analysis of variance [F(3,645 In sum, when the babies studied faces ordered in distributed blocks, the attractiveness of the faces appeared to wane in a monotonic fashion, both within and across blocks.…”
Section: Methodsmentioning
confidence: 61%
“…Based on pilot work involving 11 infants who received recognition tests identical to those in the present study, the Pearson coefficient of correlation between observed fixation times was .93, with almost identical totals for mean fixation times recorded by the two observers. This agreement is typical in laboratories using the same apparatus and measurement procedures (see Fagan, 1976, andRose et al, 1982). measures analysis of variance [F(3,645 In sum, when the babies studied faces ordered in distributed blocks, the attractiveness of the faces appeared to wane in a monotonic fashion, both within and across blocks.…”
Section: Methodsmentioning
confidence: 61%
“…The strong preference for the familiar stimulus exhibited by most of the infants is more typical of very young infants (Rose et al, 1982), not 6-8 month olds. The shift rates of visual fixations (.11 per second during familiarization, .12 during test phases) were also low relative to those reported by Rose et al (2002).…”
Section: Visual Information Processing Measuresmentioning
confidence: 83%
“…Of the original 100 infants, 26 failed to complete the minimum three trials because of excessive crying, fussing, or maternal interference (e.g., holding the infant's head in the direction of the stimuli). In addition, the data from five participants were discarded from analyses because they failed to accumulate at least 5 s of looking time during familiarization on three or more trials (Rose et al, 1982;Rose et al, 1995). We tested for differences between the infants included (3-4 trials) versus excluded (0-2 trials) by age (p = .40), sex (p = .42), head circumference (p = .64), weight (p = .42), or length (p = .09).…”
Section: Resultsmentioning
confidence: 99%
“…Isaac, & Mayes, 2004). In addition, studies with infants and adults have demonstrated that performance on the VPC task is affected by study time, retention interval, and context change in the same way that these variables affect adults' performance on other measures of declarative memory (Bahrick & Pickens, 1995;Richmond, Sowerby, Colombo, & Hayne, 2004;Robinson & Pascalis, 2004;Rose, Gottfried, Melloy-Carminar, & Bridger, 1982).…”
Section: Visual Paired-comparison Taskmentioning
confidence: 99%
“…When tested on the VPC task, the length of familiarization phase required for infants to exhibit novelty preferences decreases as a function of age (see Rose et al, 1982), so much so that researchers working with different age groups often use infant-controlled familiarization procedures (Diamond, 1995;Pascalis, de Haan, Nelson, & de Schonen, 1998), or design studies allowing younger infants longer familiarization times than older infants (Colombo, Mitchell, & Horowitz, 1988;Jacobs, 2000;Rose, Feldman, & Jankowski, 2001). Similarly, when tested on a deferred imitation task, 6-month olds require a demonstration period that is twice the length of that used with 12-month-old infants, in order to exhibit equivalent imitation performance after a delay (Barr, Dowden, & Hayne, 1996).…”
Section: Encodingmentioning
confidence: 99%